Beyond Silence: Addressing Sexual Education in Islamic Educational Institutions for a Holistic Contemporary Curriculum - Nasution, Suryadi; Pohan, Ali Jusri; Khairurrijal, Khairurrijal; Nur, Kholidah (IAIN Manado, 2025)
Sexual education within Islamic educational institutions is frequently silenced by cultural and religious stigma; however, this study unveils the potential for transformation through a holistic approach. Employing a qualitative methodology involving interviews, observations, and document analysis in Mandailing Natal, this research reveals that 68% of students, 62% of teachers, and 57% of parents endorse the teaching of sexuality within an Islamic framework. Nevertheless, existing curricula, encompassing 25% coverage in pesantrens, 15% in madrasahs, and 8% in junior high schools (SMP), fail to deliver substantial comprehension (20-35%) due to normative and fragmented approaches. A pilot implementation of a holistic model in a pesantren, integrating biology, Islamic ethics, and guided discussions, enhanced student understanding by 85% and reduced teacher stigma by 60%, with the collaboration of ulama and local elements serving as pivotal factors. This study proposes a replicable model that bridges tradition and modernity, asserting that silence can be overcome to protect adolescents from digital risks without compromising Islamic identity. Its implications are pertinent to global Islamic educational reform.